The Role of Cell Groups in Reaching Souls for the Strategy of Urban Church Development - Ficker’s Samuel Putra; Purim Marbun (Publikasi Indonesia, 2025)
In the context of urban church development, cell groups play a vital role in reaching souls and building a strong faith community. This study aims to explore the contribution of cell groups in urban church development strategies amidst complex social, cultural, and spiritual dynamics. The method used is the library research method. The results of the study indicate that cell groups are not only a place for individual spiritual growth, but also function as a bridge connecting the church with the surrounding community. Cell groups are able to create a supportive environment for members to share their faith, facilitate Bible studies, and carry out social service activities. In addition, the existence of cell groups contributes to improving the church's vision, so that evangelism and missions can be carried out more efficiently. This study also identifies challenges faced in implementing development strategies through cell groups, such as lack of member commitment and differences in vision between groups. However, with ongoing training and church support, cell groups can overcome these obstacles and become more effective in reaching new souls.